KESIAPAN SUAMI SEBAGAI PENDAMPING PERSALINAN DI PUSKESMAS PLERET KABUPATEN BANTUL YOGYAKARTA - Rizky Eka Noviana; Dian Puspitasari (MEDIA ILMU KESEHATAN, 2016)
Background: On the third trimester of pregnancy, stressors of mother, her husband and family will increasedue to their physical and emotional preparations. Social support is very important for mother prior to labor. Husband’s companion in delivery process is perceived very significant. World Health Organization (WHO) suggested that the companion in delivery processis a mother’s choice. In Indonesia 68% delivery are not accompanied by husband. A companion, in particular a significant personduring the process of delivery can shortenthe delivery period, decrease the pain level, lessen the laceration and promote APGAR’s score. Aim: To explore husbands’ readiness as companion in delivery process at Puskesmas Pleret, Bantulregency. Method: This research was a descriptivequantitative research. Samples in the research were chosen with a quota sampling method, consisted of 37 husbands of trimester III mothers and fit in with inclusion and exclusion criteria. Data were collected with a closed questionnaire and were analyzed with univariate analysis. Result: The majority of respondents were ready as companions in stage I, stage II, stage III and stage IV of the delivery process (86.5%, 70.3%, 91.9%, and 83.8%, respectively). Conclusion: The majority of husbands wereready to accompanythe delivery process at Puskesmas Pleret, Bantul regency(70,3% respondents). Keywords: Readiness, companion of delivery.